Gender equity in the electoral process: the context of the electoral process of the Judiciary in Mexico - Castro Figueroa , Fernando Manuel (2025)
This article analyzes gender equity in the context of the electoral process within the Mexican judiciary. The study examines the problem of women's representation in positions of power and decision-making, as well as the structural challenges that persist in achieving full inclusion of women in the judicial system.  The objective is to assess the impact of recent structural reforms on gender equality within the judiciary. The methodology used is based on a documentary and regulatory analysis, reviewing legal reforms, academic studies, institutional reports, and official statistics. The main findings highlight significant progress in female participation but also reveal structural barriers that continue to limit gender equity in judicial selection and appointment processes. Finally, the article underscores the importance of ensuring gender parity as a fundamental mechanism to strengthen democracy and guarantee equal access to judicial representation bodies.